Biodiversity loss, the causes, the state and basic form of nature protection in Spain and Poland - Soler Luque, Zaida; Kostecka, Joanna (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2018)
The loss of biodiversity is a huge problem over recent years and is expected to continue. This is mainly due to human activity. Causes can be divided into direct; such as land use, pollution or climate change, and indirect, including demographic factors as well as economic and government issues. In order to avoid a further decline of biodiversity, nature conservation is undertaken, which plays a key role in preserving natural ecosystems. The aim of this review was to show the problem of loss of biodiversity and to compare the structure of nature conservation forms in Spain and Poland.

Utrata bioróżnorodności to ogromny problem ostatnich lat i przewiduje się, że będzie miała nadal miejsce. Wynika to głównie z działalności człowieka. Przyczyny mogą być podzielone na bezpośrednie; takie jak użytkowanie gruntów, zanieczyszczenie środowiska lub zmiana klimatu, i pośrednie, co obejmuje czynniki demograficzne a także kwestie ekonomiczne i rządowe. W celu uniknięcia dalszego zaniku różnorodności biologicznej podejmowana jest ochrona przyrody, co odgrywa kluczową rolę w zachowaniu naturalnych ekosystemów. Celem opracowania było ukazanie problemu utraty różnorodności biologicznej oraz porównanie struktury form ochrony przyrody w Hiszpanii i Polsce.
Keywords: biodiversity loss; causes; state; nature protection forms; utrata różnorodności biologicznej; przyczyny; stan; formy ochrony przyrody